A few sketches about #CONNEXIONS24 (or welcome to #CONNEXIONS24) - Klynina, Tetiana (Ukrainian Cultural Studies, 2024)
March 18-20, 2024, The University of Texas at Austin, USA, Texas, hosted the annual #Connexions conference.